Enhancing Student’s Writing Ability In Paragraph Writing Through An Outline Strategy At Primary Level - Hassan Ramzan; Muhammad Hafeez (Indonesian Journal of Basic Education, 2021)
This research was based on classroom action research. The main objective of this research was to know the improvement in students writing skill in writing paragraph through an outline strategy. This research was done at fifth grade students of five Government Primary Schools located at D. G. Khan city. The participants of this research were 15 students of grade five. Such participants were selected through random sampling technique. The obtained data was analyzed in percentage. Pre-Test and Post-Test used as an instrument in this research. In both Pre-Test and Post-Test required items like paragraph title writing, grammar, spelling and total sentences (length) of paragraph were same. In Pre-Test, outline strategy in paragraph writing was not employed but in Post-Test such strategy was used. According to findings, in Pre-Test students writing paragraph were 20.00%, 26.66%, 20.00%, 26.66% (Good), 46.66%, 20.00%, 33.33%, 33.33% (Average), 33.33%, 53.33%, 46.66%, 40.00% (Weak) in paragraph writing title, proper use of grammar, correct spelling and total sentences (length) of paragraph, respectively. After Pre-Test, instructor taught participants about writing paragraph through an outline strategy for a period of 4 weeks and then conducted Post-Test. In this test, participants writing paragraph through an outline strategy were 46.66%, 53.33%, 60.00%, 53.33% (Good), 40.00%, 26.66%, 33.33%, 40.00% (Average), 13.33%, 20.00%, 6.66%, 6.66% (Weak) in paragraph writing title, proper use of grammar, correct spelling and total sentences (length) of paragraph, respectively. This action-based research demonstrated that outline strategy can improve the students writing skills.